2009
DOI: 10.1007/s00264-009-0748-7
|View full text |Cite
|
Sign up to set email alerts
|

Zoledronate reduces unwanted bone resorption in intercalary bone allografts

Abstract: Bone allografts are often hampered by graft incorporation and poor host bone formation. Bisphosphonates, synthetic pyrophosphate analogs, have shown promise in inhibiting bone resorption in human and animal trials. Some in vitro studies have suggested that high dose bisphosphonate may also inhibit bone formation, leading to our hypothesis that an ideal dose of bisphosphonate in allografts could protect allografts from resorption. We transplanted intercalary allografts in to the segmental defect of the rat femu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…demonstrated that ZOL reduces unwanted bone resorption in intercalary bone allografts. The optimal soaking concentration for the allografts was 0.03 mmol ZOL with a significant increase in bone‐mass density . Tanzer et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…demonstrated that ZOL reduces unwanted bone resorption in intercalary bone allografts. The optimal soaking concentration for the allografts was 0.03 mmol ZOL with a significant increase in bone‐mass density . Tanzer et al .…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism by which bisphosphonates work in combination with calcium systems in vivo is briefly described as follows: Seo et al . demonstrated that the potent N‐containing bisphosphonate ZOL reduces unwanted bone resorption processes . ZOL inhibits osteoclastic activity and regulates cell proliferation, differentiation and gene expression in osteoblasts due to a stimulation of bone formation .…”
Section: Introductionmentioning
confidence: 99%
“…Among BPs currently in use, zoledronate, which is most frequently administered intravenously, has the highest binding affinity with Hydroxyapatite. Moreover, zoledronate is characterized by the most rapid onset and longest lasting action of all BPs and as such constitutes a promising candidate for use in dental applications (23–25). Under the assumption that zoledronate pharmacological effects on the inflammatory inhibition are superior to etidronate and the alendronate, we tested the treatment effects by setting the control group as the negative control and alendronate group as the positive control.…”
mentioning
confidence: 99%
“…To test our hypothesis, we used a rat femoral segmental defect model, which has been used previously to test the effects of various materials and agents on bone growth. [9][10][11][12][13][14] We created a 5 mm femoral defect, replaced the defect with appropriate grafts, and repaired the construct using an intramedullary K-wire. Segmental defects of 5 mm in the rat femurs have been shown to result consistently in nonunions, both radiographically and clinically.…”
Section: Introductionmentioning
confidence: 99%